Two dimensional triptycene end-capping and its influence on the self-assembly of quinoxalinophenanthrophenazines : dedicated to the special issue of Optoelectronic functional material - Roß, Lisa; Reitemeier, Julius; Ghalami, Farhad; Zhang, Wen-Shan; Gross, Jürgen H.; Rominger, Frank; Elbert, Sven; Schröder, Rasmus R.; Elstner, Marcus; Mastalerz, Michael (Chinese journal of chemistry, 2023)
Comprehensive Summary In this report we investigated two-dimensionally triptycene end-capped QPPs in terms of their solution and solid-state behavior. For this purpose, a triphenylene based ortho-diamine decorated with two triptycenyl units as well as a phenylene diamine with two non-annulated triptycene units have been synthesized. Sequences of condensation reactions with a pyrene-based tetraketone and ortho-diamines yielded a series of QPPs and UV/Vis investigations of the corresponding compounds led to the conclusion, that the QPPs form dimers in solution, which was further supported by MALDI-TIMS-TOF-MS. Single-crystal X-ray analysis of the triply and quadruply triptycene end-capped QPPs furthermore showed short π-π-distances of 3.3—3.4 Å and a perfect shape match during the dimerization of the triply triptycenyl end-capped QPP making it possible synthon for crystal engineering.
Gesehen am 05.12.2024